2019
DOI: 10.15171/jhp.2019.33
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituents of the Gynura procumbens ethanol leaf extract and its fractions and their effects on viability of macrophages

Abstract: Introduction: Gynura procumbens (GP) is a medicinal plant with numerous beneficial pharmacological activities. The aim of this study was to identify the bioactive phytoconstituents in GP ethanol extract and hexane, chloroform, ethyl acetate, and aqueous fractions of GP, and also to evaluate the cell viability of GP ethanol extract and its fractions-treated RAW264.7 cells.Methods: The ethanol GP leaf extract was prepared and further subjected to fractionation. The cell viability of GP ethanol extract and its fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…at Kepala Batas, Penang, Malaysia (GPS coordinate: 5.5210° N, 100.4370° E) and a sample of the plant was identified by a botanist from the School of Biological Sciences, Universiti Sains Malaysia and deposited at the USM Herbarium with voucher number of 11753. The preparation of GP ethanol extract and its fractions were described by Manogaran et al (6,13).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…at Kepala Batas, Penang, Malaysia (GPS coordinate: 5.5210° N, 100.4370° E) and a sample of the plant was identified by a botanist from the School of Biological Sciences, Universiti Sains Malaysia and deposited at the USM Herbarium with voucher number of 11753. The preparation of GP ethanol extract and its fractions were described by Manogaran et al (6,13).…”
Section: Animalsmentioning
confidence: 99%
“…These pharmacological benefits were induced by chemical constituents found in GP such as kaempferol, flavonoids, terpenoids, tannins, saponins, rutin, and sterol glycosides (4,5). Recently, LC-MS/MS analysis of GP ethanol extract and its fractions exhibited various biochemical compounds originated from flavonoids, fatty acids, sesquiterpenoids, and the products of chlorophyll breakdown (6).…”
Section: Introductionmentioning
confidence: 99%
“…(GP) (Asteraceae), commonly known as 'Sambung nyawa' in Malaysia, is used traditionally to treat various ailments, such as fever, rashes, constipation, high blood pressure, diabetes mellitus, hypertension, urinary tract infection, and kidney disease (Puangpronp et al 2010;Mou and Dash 2016). Previous studies have revealed the active constituents of GP extract were made up of flavonoids, saponins, tannins, terpenoids and sterol glycosides (Kaewseejan et al 2015;Ashraf 2019;Manogaran et al 2019). Other studies reported that the leaf extract of GP contained several potential antioxidant components including kaempferol, astragalin, kaempferol-3-Orutinoside, rutin, caffeic acid and chlorogenic acid (Rosidah et al 2008;Ahmad Nazri et al 2019).…”
Section: Introductionmentioning
confidence: 98%
“… 2015 ; Ashraf 2019 ; Manogaran et al. 2019 ). Other studies reported that the leaf extract of GP contained several potential antioxidant components including kaempferol, astragalin, kaempferol-3- O -rutinoside, rutin, caffeic acid and chlorogenic acid (Rosidah et al.…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity is affected by the presence of its metabolites. The detected bioactive metabolites in the leaves of G. procumbens include phenolic acids, flavonoids, saponins, tannins, terpenoids, and steroid glycosides [4][5][6].…”
Section: ■ Introductionmentioning
confidence: 99%